2017
DOI: 10.1155/2017/9658018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of Antimycotics Used for Invasive Fungal Infections: In Vitro Results

Abstract: Purpose. Drug-induced liver injury (DILI) is the most common cause of liver injury and a serious clinical problem; antimycotics are involved in approximately 3% of all DILI cases. The hepatotoxicity of many drugs, including the antimycotics, is poorly screened in human models. Methods. In a standardized assay the cytotoxicity on hepatocytes of different concentrations (Cmax, 5x Cmax, and 10x Cmax) of the antimycotics used for systemic infections was tested. Anidulafungin (ANI), liposomal amphotericerin B (L-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…In vitro studies have shown that some antimycotics like fluconazole and anidulafungin have got a dose-dependent effect on albumin synthesis. High concentrations of these drugs can cause cellular necrosis [15]. Our patient with complex pathophysiological changes due to sepsis showed a significant decrease in serum albumin.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In vitro studies have shown that some antimycotics like fluconazole and anidulafungin have got a dose-dependent effect on albumin synthesis. High concentrations of these drugs can cause cellular necrosis [15]. Our patient with complex pathophysiological changes due to sepsis showed a significant decrease in serum albumin.…”
Section: Discussionmentioning
confidence: 61%
“…Maintaining a regular dose of 50 mg/d may lead to toxic blood concentrations which may result in drug-induced liver injury (DILI) [14]. Vitality, viability, and function of hepatocytes is remarkedly impaired in vitro, when echinocandins are overdosed [15]. e protein amount seems to matter, as 95% of caspofungin are bound to plasma proteins, especially albumin [16].…”
Section: Discussionmentioning
confidence: 99%
“…Here we study the effect of albumin on HepG2/C3A hepatocellular carcinoma cell line, a contact inhibited subclone of the HepG2 cell line (Aden et al, 1979) that retains some physiological functions of normal hepatocytes (Kelly et al, 1992;Nibourg et al, 2012). The HepG2/C3A cells are used as a model cell line for studying parenchymal biosynthesis (Knowles, Howe & Aden, 1980;Zannis et al, 1981;Nibourg et al, 2012) and screening for cytotoxicity of drug compounds for side effects involving liver injury (Gaskell et al, 2016;Doß et al, 2017). The cell line has also been considered for testing clinical samples in screening for diseases (Sauer et al, 2012;Sauer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although similar studies have been previously performed on the HepG2 hepatocellular carcinoma parent clone demonstrating that albumin prevents proliferation (Nojiri & Joh, 2014;Bağırsakçı et al, 2017), experiments in this study were carried out on the HepG2/C3A subclone and were contradictory to these earlier findings. Since HepG2/C3A cell line is commonly used as a model for drug testing (Gaskell et al, 2016;Doß et al, 2017), it is justifiable to have a basic understanding of the effects of albumin on HepG2/C3A cells when testing albumin bound drugs. This primary approach offers a platform and a control method when studying the effects of drug bound albumin and pathologically modified albumin on cell proliferation as well as cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Here we study the effect of albumin on HepG2/C3A hepatocellular carcinoma cell line, a contact inhibited subclone of the HepG2 cell line (Aden et al, 1979) that retains some physiological functions of normal hepatocytes (Kelly et al, 1992;Nibourg et al, 2012). The HepG2/C3A cells are used as a model cell line for studying parenchymal biosynthesis (Knowles, Howe & Aden, 1980;Zannis et al, 1981;Nibourg et al, 2012) and screening for cytotoxicity of drug compounds for side effects involving liver injury (Gaskell et al, 2016;Doß et al, 2017). The cell line has also been considered for testing clinical samples in screening for diseases (Sauer et al, 2012(Sauer et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%